Pengaruh Pengungkapan Good Corporate Governance Terhadap Nilai Perusahaan Pada Badan Usaha Milik Negara Yang Terdaftar Di Bursa Efek Indonesia Perioda 2013-2017 - Stevi Jimry Poluan; Arya Aditya Wicaksono (Universitas Putera Batam, 2019)
This study aims to prove the impact of Good Corporate Governance on Firm Value in Badan Usaha Milik Negara that listed in Indonesian Stock Exchange. This study used 4 varibles that represented Good Corporate Governance which is Managerial Ownership, Institusional Ownership, Board of Independent Commissioner, and Audit Committee. Meanwhile Tobin’s Q ratio used to counted Firm Value. Population of this research are all Badan Usaha Milik Negara that listed in Indonesian Stock Exchange on 2013 until 2017. There are 20 firm are listed. The total samples are 16 firms selected by using purposive sampling method. Data anlysis and hypothesis testing using multiple regression. From 4 variable that used in this research only 2 that had an effect on firm value. There were Institusional Ownership and Audit Committee. This research prove that Institusional Ownership has a positive and significant effect on firm value. Audit Committee had a negative and insignificant effect on firm value. Other 2 variable like Managerial Ownership, Board of Independent Commissioner has not effect on firm value, while Audit Committee has negative effect on firm value.